2013
DOI: 10.1093/hmg/ddt239
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies loci affecting blood copper, selenium and zinc

Abstract: Genetic variation affecting absorption, distribution or excretion of essential trace elements may lead to health effects related to sub-clinical deficiency. We have tested for allelic effects of single-nucleotide polymorphisms (SNPs) on blood copper, selenium and zinc in a genome-wide association study using two adult cohorts from Australia and the UK. Participants were recruited in Australia from twins and their families and in the UK from pregnant women. We measured erythrocyte Cu, Se and Zn (Australian samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
156
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(177 citation statements)
references
References 47 publications
5
156
0
Order By: Relevance
“…Currently, there is no internationally acceptable value or range for plasma selenium concentration in the general population. Thus, it remains to be elucidated whether or to what extent the discrepancies regarding plasma selenium concentrations could be explained by its exposure levels, effects of genetic predisposition and other predisposing factors on its metabolism39, between-laboratory differences in methods (ICP-MS vselectrothermal atomic absorption spectrometry) and measurement errors, or variations in population characteristics among studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is no internationally acceptable value or range for plasma selenium concentration in the general population. Thus, it remains to be elucidated whether or to what extent the discrepancies regarding plasma selenium concentrations could be explained by its exposure levels, effects of genetic predisposition and other predisposing factors on its metabolism39, between-laboratory differences in methods (ICP-MS vselectrothermal atomic absorption spectrometry) and measurement errors, or variations in population characteristics among studies.…”
Section: Discussionmentioning
confidence: 99%
“…For the general population, the primary exposure pathways, in order of decreasing relative proportions, are food, water, and air39. Some studies found high amounts of selenium in foods like nuts, seafood, meats and wheat40.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in trace element concentration could result from soil, geographical location, food preparation and processing, food accessibility, cultural practices, pollution, or ethnic differences in body composition and genetics [7]. A recent genome-wide association study has identified loci affecting blood Cu, Se, and Zn from 2603 Australian and 2874 British participants [4]. …”
Section: Discussionmentioning
confidence: 99%
“…Nutrient status, including the bioavailability and concentration of trace elements, is known to be influenced by many physiological and diet factors, such as soil, geographical location, food preparation, pollution, body composition, and ethnicity [4,5,6]. During pregnancy, both physiological variables and diet influence the availability of trace elements for digestion, absorption, and utilization [7].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with incorrect sex assignments, unusual genome-wide or X-chromosome heterozygosity, disproportionate levels of individual missingness (>5%), evidence of cryptic relatedness (>12.5% identity-by-descent [IBD]), or those of non-European ancestry determined from multidimensional scaling analysis seeded with individuals from the International HapMap project [29] were excluded. The resulting dataset consisted of 8340 individuals [30]. …”
Section: Methodsmentioning
confidence: 99%